Artificial Intelligence Based Halal Compliance Model Civil Law Perspective - Rafianti, Fitri; Erika, Winda; Damanik, Rusli Efendi; Harahap, Aswindari (Cattleya Darmaya Fortuna, 2025)
The purpose of this study is to examine and analyze the role of the